2022
DOI: 10.1186/s12876-022-02539-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of Clinical Practice Guidelines (CPG) for the diagnosis and treatment of inflammatory bowel disease using the AGREE II instrument: a systematic review

Abstract: Background The incidence and diagnosis of inflammatory bowel disease (IBD) has increased considerably in recent years. Many clinical practice guidelines (CPG) have been developed for the management of this disease across different clinical contexts, however, little evidence exists on their methodological quality. Therefore, we aimed to systematically evaluate the quality of CPGs for the diagnosis and treatment of IBD using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…One study conducted a systematic review of IBD diagnosis and/or treatment CPGs, applying the AGREE II instrument and finding similar average scaled domain percentage findings: clarity of presentation (85.58%), scope and purpose (84.51%), editorial independence (62.02%), rigour of development (69.95%), stakeholder involvement (60.90%), and applicability (26.60%) [ 87 ]. The study’s authors concluded that the quality of most evaluated CPGs was acceptable, though there was room for improvement in the domains of stakeholder participation and applicability [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study conducted a systematic review of IBD diagnosis and/or treatment CPGs, applying the AGREE II instrument and finding similar average scaled domain percentage findings: clarity of presentation (85.58%), scope and purpose (84.51%), editorial independence (62.02%), rigour of development (69.95%), stakeholder involvement (60.90%), and applicability (26.60%) [ 87 ]. The study’s authors concluded that the quality of most evaluated CPGs was acceptable, though there was room for improvement in the domains of stakeholder participation and applicability [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted a systematic review of IBD diagnosis and/or treatment CPGs, applying the AGREE II instrument and finding similar average scaled domain percentage findings: clarity of presentation (85.58%), scope and purpose (84.51%), editorial independence (62.02%), rigour of development (69.95%), stakeholder involvement (60.90%), and applicability (26.60%) [ 87 ]. The study’s authors concluded that the quality of most evaluated CPGs was acceptable, though there was room for improvement in the domains of stakeholder participation and applicability [ 87 ]. Another systematic review applied the AGREE II instrument to pharmacological therapy recommendations in IBD CPGs, though the pharmacological review differed considerably in domains of editorial independence (94.0%), applicability (45.8%), and stakeholder involvement (38.9%) [ 88 ] as compared to this present review.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Other barriers exist such as the quantity of guidelines available and variations in the quality and the possibility of contradictory evidence. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review categorises the barriers into political and social factors (requirement of a leader to champion implementation), health system organisation factors (lack of time), guideline factors (clarity and access), health professional factors (confidence and knowledge) and patient factors (social and cultural influence) [19]. Other barriers exist such as the quantity of guidelines available and variations in the quality and the possibility of contradictory evidence [20,21].…”
Section: Introductionmentioning
confidence: 99%